Case Report: KLHL11 encephalitis in a female patient with dual primary malignancies of breast and lung cancer: response to FcRn inhibitor therapy - Li, Yapeng; Xing, Haoran; Cao, Zhentang; Cui, Pan; Zhao, Lu (Frontiers in Immunology, 2025)
Kelch-like protein 11 (KLHL11) encephalitis is a rare clinical condition characterized by autoimmune-mediated encephalitis associated with the presence of KLHL11 antibodies, which commonly presents with ataxia, diplopia, vertigo, hearing loss, and seizures. While the link between this high-risk paraneoplastic autoantibody and male testicular germ cell tumors is well-established, female cases are rare, and no case of ductal breast carcinoma or dual primary malignancies have been reported. The disease is generally resistant to conventional therapies. In this study, we reported a case of KLHL11 encephalitis in a female patient presenting with fever, seizures, and ataxia, alongside dual primary malignancies: ductal breast carcinoma and pulmonary adenocarcinoma. Following immunotherapy with a neonatal Fc receptor (FcRn) inhibitor (efgartigimod) and resection of tumors, the patient achieved complete symptomatic remission with no recurrence. Current studies showed that KLHL11 encephalitis contributed to pathogenesis through cytotoxic T-cell-mediated neuronal injury and loss. However, in this case, rapid clinical improvement was observed after FcRn inhibitor therapy. This is the first report of FcRn inhibitor in the treatment of KLHL11 encephalitis. This case demonstrated a rare association of KLHL11 encephalitis with breast and lung cancer, and expanded on the clinical manifestations, associated tumor types, and treatment options of KLHL11 encephalitis in women.